The Prevalence and Subtype Distribution of Hepatitis C Virus Infection among Hemodialysis Patients in a Private Hospital in Surabaya, Indonesia - MOCHAMAD AMIN; JUNIASTUTI .; TAKAKO UTSUMI; YOSHIHIKO YANO; MOCHAMAD YUSUF; MOCHAMMAD THAHA; PRIYO BUDI PURWONO; RETNO HANDAJANI; SOETJIPTO .; HAK HOTTA; YOSHITAKE HAYASHI; MARIA INGE LUSIDA (Indonesian Society for microbiology, 2012)
The prevalence of hepatitis C virus (HCV) infection has been as high as approximately 80% in patients with maintenance hemodialysis in public hospitals in Indonesia. However, the prevalence in private hospitals has not been examined yet. The aim of this study was to investigate the prevalence of anti-HCV antibody and the subtype distribution in patients with hemodialysis in a private hospital in Surabaya, Indonesia. Sera were obtained from 41 hemodialysis patients in a private hospital in Surabaya. The positive prevalence of anti-HCV antibody was carried out by the enzyme-linked immunosorbent assay (ELISA). Anti-HCV-positive sera were subjected to reverse transcription-PCR (RT-PCR) to detect HCV RNA and then direct sequencing. The HCV subtype was examined by phylogenetic analysis. Twenty five patients (61%) out of 41 were positive for anti-HCV antibody, and HCV-RNA was detected in 19 patients. The positive prevalence of anti-HCV antibody was 7.7% (one out of 13 patients) among patients who had undergone hemodialysis for less than one year, whereas it was 85.7% (24 out of 28 patients) among patients who had undergone hemodialysis for over one year. Phylogenetic analysis revealed HCV-1a (52.6%) was the most common subtype, followed by 1b (15.8%), 1c (15.8%), 2a (5.3%), and 3k (5.3%). In conclusion, the prevalence of HCV infection among hemodialysis patients in a private hospital was as high as that in general hospitals. The predominant subtype was HCV-1a, which is in accordance with the previous studies in general hospitals in Surabaya, Indonesia.